Building safer cities : the future of disaster risk - Kreimer, Alcira; Arnold, Margaret, 1965-; Carlin, Anne (Disaster risk management series, 2003)
In developing countries, disasters can cause major setbacks to economic and social development, inflict massive casualties, and cause the diversion of funds from development to emergency relief and recovery.